An Analysis of Slang Word on Comment in Selena Gomez’s Instagram Account - Desmi Khoirotunnisak; Eka Fanti Sulistiyaningsih (Universitas An Nuur, 2023)
Slang is an informal language used by a certain community or group. The aim of this research is to identify the most frequently used slang words, their types, meanings, and social factors from comments in Selena Gomez's Instagram account. Descriptive qualitative methodology is used in this research. The phenomenon of slang words is the subject of this research. The researcher found slang words in Instagram comments. The primary source of data for this research is comment in Selena Gomez's Instagram account. In this research, books, journals, and other sources that provide data to support this research will be used as the secondary data source. The result of this research are five types of slang according to (Allan and Burridge, 2006), from 50 data of slang words in column comments with total frequencies of as much as 412 words, namely acronym was the most appeared slang in this research with 139 or 33,74%. Then clipping, it is 118 words 28,71%. After that, it is imitative, it is around 66 or 16,05%. Fresh and creative are 59 frequencies or 14.3%. While flippant is the least appeared with 30 or 7,2%. The social factors that influenced the use of slang word as follows the level of age, environment, and education. As a result, slang is occasionally used as a language among individuals. Especially, when they have multiple goals like be creative, fashionable, fun, and distinct from the previous generation.